Analisa Terhadap Stabilitas dan Olah Gerak pada Kapal Ferry Ro-Ro Akibat Penambahan Panjang - Yanuar Eka Erida; Raden Dimas Endro Witjonarko; Emie Santoso (Politeknik Perkapalan Negeri Surabaya, 2020)
In this study the authors will analyze the stability and also analyze the sea condition index of the shipafter undergoing modification in addition of length. The analysis continued on checking the stability conditions ofthe ship after undergoing modification of the addition of length by simulating the model and loading on theMaxsurf software, a simulation of loading given when conditions ship departure and arrival and also examine thecondition of the waters in which the ship can sail safely according to seakeeping criteria based on Nordforsk 1987rule. The ship after modification in all loading conditions meets the stability criteria IMO intact stability and hasbetter stability performance than the ship before modification.The ship after modification is not suitable to be onthe Lombok Strait shipping route in full load state because in the calculation the ship has a deck wetnessprobability that exceeds 5% according to Nordfordsk 1987 regulations.